Characteristics of Infarct and Hemorrhagic Stroke Patients Who Died at RSUD Bayu Asih Purwakarta, January–December 2024 - Komarudin, Ahmad Zakki; Widodo, Taufan Putra; Astuti, Murti; Syam, Zuhaira; Hedwar, Ganda Septianda (Jurnal Indonesia Sosial Sains, 2025)
Stroke is the leading cause of death globally, including in Indonesia, with two main types, namely infarctive stroke and hemorrhagic stroke. This research aims to determine the risk factors for stroke, infarction, and hemorrhagic patients who die at Bayu Asih Purwakarta Hospital. This research was an observational analytical study with a cross-sectional retrospective design using medical record data of stroke patients who died during the period January–December 2024. Data were analyzed univariately using Microsoft Excel and SPSS v30.1. Results: Of the 227 stroke patients who died, 117 (51.5%) had infarctive stroke and 110 (48.5%) had hemorrhagic stroke. The age of >66 years dominates infarction deaths, while the age of 46–55 years is most commonly found in hemorrhagic strokes. Women die more from both types of stroke. Stage 2 hypertension dominates infarctive stroke, while hypertension crisis is most common in hemorrhagic stroke. The majority of heart attack patients have a history of diabetes mellitus, while hemorrhagic strokes are more common without a history of DM. NIHSS scores indicate that most patients have very severe neurological deficits. Conclusion: Most of the deaths due to stroke at Bayu Asih Purwakarta Hospital most occur in elderly patients, especially in infarct stroke cases. While hemorrhagic strokes are more common at younger ages with very high blood pressure and higher NIHSS scores. The female gender also shows a higher mortality trend, in line with national findings. These factors can be used to prioritize early management and secondary prevention of stroke, especially in high-risk groups.